2015
DOI: 10.3389/fnagi.2015.00160
|View full text |Cite
|
Sign up to set email alerts
|

Changes in voiding behavior in a mouse model of Alzheimer’s disease

Abstract: Besides cognitive decline and behavioral alteration, urinary incontinence often occurs in patients suffering from Alzheimer’s disease (AD). To determine whether the transgenic mouse model of AD, APP/PS1 (APPSL/PS1M146L) mouse, shows alteration of the urinary bladder function and anxiety, as for patients with AD, we examined the urinary marking behavior in relation to affective behavior. At 18 months of age voiding behavior of APP/PS1 and wild type (WT) mice was assessed by using a modified filter paper assay i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Body weights of mice had no significant change in the whole experimental period (Figure S2B). It is reported that APP/PS1 mice fail to construct nests 27 and display an increased locomotor activity compared with wild-type mice 28, 29. The nesting scores of the PS1/APP mice improved significantly with both T600 and L + T600 treatments (p < 0.01 for T600, p < 0.01 for L + T600; Figures S3A and S3B).…”
Section: Resultsmentioning
confidence: 93%
“…Body weights of mice had no significant change in the whole experimental period (Figure S2B). It is reported that APP/PS1 mice fail to construct nests 27 and display an increased locomotor activity compared with wild-type mice 28, 29. The nesting scores of the PS1/APP mice improved significantly with both T600 and L + T600 treatments (p < 0.01 for T600, p < 0.01 for L + T600; Figures S3A and S3B).…”
Section: Resultsmentioning
confidence: 93%
“…A recent study showed an altered voiding behavior in a transgenic mouse model of AD [52]. The authors explained that the reason of voiding alterations in the APP/presenilin 1 of mice could be because of the changes in related to anxiety and general locomotor behavior, specific of AD.…”
Section: Adult Neurogenesis In Alzheimer Diseasementioning
confidence: 99%
“…In patients with cerebral infarction, retention of urine caused by areflexic bladder, urinary urgency, or urinary frequency caused by detrusor hyperreflexia occurs frequently. However, there is a shortage of satisfactory treatments to control and improve neurogenic bladder induced by such neurological diseases [3,4]. …”
mentioning
confidence: 99%